The Influence of Content Personalization and Social Interaction on Customer Satisfaction Through Purch - Muhammad Farhan Ariq Pramanda; Anjas Apriana; Dr. Osly Usman, M.Bus Syst (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
Research on the influence of Content Personalization and Social Interaction on purchasing decisions and customer satisfaction at the Feih Alharam Brand in the context of the digital era and globalization. This brand is unique with its exclusive perfume products and other product offerings from Saudi Arabia. Prioritize social interaction through social media, understand customer preferences, and strive to maintain competitive advantage. This research model will be analyzed using the Partial Least Square (PLS) method and assisted by SmartPLS 3.0 software. PLS is an alternative method of Structural Equation Modeling (SEM). The research results show that Personalized Content has a positive effect on purchasing decisions for Feih Alharam products. Social interaction also has a positive influence on purchasing decisions and consumer satisfaction. Purchasing decisions have a positive effect on consumer satisfaction. However, Content Personalization has a negative effect on consumer satisfaction. Social interaction has a positive effect on consumer satisfaction through purchasing decisions for Feih Alharam products. The practical implication of this research is to provide input to Feih Alharam to increase personalization of content and interactions to strengthen purchasing decisions and consumer satisfaction. Suggestions for institutions are to improve more characteristic content personalization indicators. For future researchers, it is recommended to continue research in different business fields and expand references and preparation during research.